Analysis of Dynamic Framework to Prevent Potential Post-Migration Conflict of Rohingya Ethnic in Aceh - Anas, Muhammad Riza Fathu; Sukendro, Achmed; Malik, Ichsan; Widodo, Pujo; Chandra, Arlina Alfiani (Journal of Law, Politic and Humanities, 2024)
The lack of recognition for the Rohingya ethnic group by Myanmar and Bangladesh had led to the influx of Rohingya refugees into the Aceh region of Indonesia. This research aimed to analyze the dynamics of conflict post-migration of the Rohingya ethnic group by utilizing the Dynamic Framework, which identified components of escalation and de-escalation, conflict factors, conflict actors, stakeholders, and political will. The methodology employed in this research was a qualitative approach with data collected through a literature review related to the research topic. The findings indicated that the potential for conflict arose post-migration of the Rohingya ethnic group due to criminal activities committed by the refugees while in Aceh, resulting from the government's failure to impose strict sanctions and the unclear status of the Rohingya refugees. Local community and students, responded negatively to this situation, necessitating further involvement from the central and local governments to prevent potential conflicts between Rohingya refugees and local residents. Although Indonesia had not ratified the 1951 Vienna Convention and its 1967 Protocol, Indonesia, through Presidential Regulation No. 125 of 2016, continued facilitate the Rohingya ethnic group humanely without neglecting the interests of local residents to prevent potential conflicts from escalating.